2018
DOI: 10.1186/s12890-018-0590-z
|View full text |Cite
|
Sign up to set email alerts
|

Secondary pulmonary alveolar proteinosis: a single-center retrospective study (a case series and literature review)

Abstract: BackgroundSecondary pulmonary alveolar proteinosis (sPAP) is an extremely rare disease. The clinical features of sPAP patients remain to be summarizeds. MethodsPatients pathologically diagnosed with PAP and with negative results for anti-granulocyte macrophage colony stimulating factor (GM-CSF) autoantibodies from Peking Union Medical College Hospital between January 2000 and July 2016 were retrospectively studied. The PubMed database was also searched for literature to collect published cases.ResultsIn our ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…In our PAP patients, mycobacterial infection was accompanied by about 5%. Several studies reported the association between tuberculosis (TB) and PAP [26][27][28][29]. Zhang et al reported that TB infection was identified in 44% of secondary PAP patients (n = 9) [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our PAP patients, mycobacterial infection was accompanied by about 5%. Several studies reported the association between tuberculosis (TB) and PAP [26][27][28][29]. Zhang et al reported that TB infection was identified in 44% of secondary PAP patients (n = 9) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported the association between tuberculosis (TB) and PAP [26][27][28][29]. Zhang et al reported that TB infection was identified in 44% of secondary PAP patients (n = 9) [26]. Some coexisting cases of PAP and TB have also been reported [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Myelodysplastic syndromes and chronic myeloid leukemia are the most commonly reported hematological disorders associated with PAP syndrome. 2,[45][46][47][48][49][50][51][52][53][54] Although the pathogenic mechanisms underlying secondary PAP are not well understood, it is apparent that most predisposing conditions associated with secondary PAP result in reduced macrophage numbers or function, hence it is likely that the ability of alveolar macrophages to clear surfactant is compromised.…”
Section: Pathogenesis Of Secondary Papmentioning
confidence: 99%
“…Pulmonary alveolar proteinosis (PAP), first described by Rosen et al (1) in 1958, is a rare diffuse lung disease of idiopathic etiology. Its estimated prevalence is about one in 3.7-6.9 × 10 6 with a male/female ratio of 1:1 to 2:1 (2)(3)(4)(5). Most patients are diagnosed between 20 and 50 years of age (2,(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Its estimated prevalence is about one in 3.7-6.9 × 10 6 with a male/female ratio of 1:1 to 2:1 (2)(3)(4)(5). Most patients are diagnosed between 20 and 50 years of age (2,(4)(5)(6). PAP is pathologically characterized by the presence of massive, amorphous, insoluble phospholipid-rich protein deposition in the alveolar and bronchial cavities.…”
Section: Introductionmentioning
confidence: 99%